"The Road We Travel": Developing a co‐produced narrative for a photovoice project. Issue 4 (19th November 2020) - Barry, Jennifer; Monahan, Christine; Monahan, Mark; Murphy, Rebecca; Ferguson, Sharon; Lee, Kelley; Bennett, Anna; Gibbons, Patrick; Higgins, Agnes
Accessible Summary: What is known on the subject?: PhotoVoice as a participatory methodology has been used within mental health to support marginalized communities in addressing the challenges they encounter. The PhotoVoice methodology aims to encourage and foster collaborative and equal partnerships. However, reports of previous projects highlight that not every stage of the process remains participant‐centric. There is limited reporting on participant involvement in the latter stages of projects, such as exhibition design. What the paper adds to existing knowledge?: It provides a detailed description of the phases involved in planning and executing a mental health PhotoVoice project. It provides an illustration of how collaborative partnerships can extend into the design and construction of a photography exhibition and its narrative. What are the implications for practice?: PhotoVoice is an ideal methodology for use within the field of mental health nursing as it promotes service user inclusion in research, places value on lived experiences and provides a creative medium through which service users and family members can advocate for themselves and others. PhotoVoice is an effective and creative methodology for disseminating and communicating both the individual and collective outcomes to the general public. When implementing this methodology, clinicians and researchers need to be cognisant of the necessity to include participants as equal partners at every stage, including in the design of photography exhibitions and disseminating the findings to academic and public audiences. Abstract: Introduction: PhotoVoice is a participatory methodology in which marginalized communities represent their lived experiences through photography. While the methodology aims to foster partnerships throughout all phases, the literature suggests that in the field of mental health, some phases are often completed without participant involvement. Aims: This paper elaborates on how the PhotoVoice method was used to engage service users and family members around their experience of involvement in a co‐produced and co‐facilitated mental health education intervention, in order to enhance public and policymakers knowledge of the project. Methods: Ten participants were recruited and trained in the PhotoVoice method. Participants documented, through photography, their experiences of involvement in the education intervention. Following this, participants came together to co‐produce and disseminate the photography exhibition to the public. Results: PhotoVoice proved to be a flexible and creative method by which to include marginalized groups. By adhering to the collaborative principles of the methodology, service users and family members can retain decision‐making power from the project's inception to its conclusion. Implications for Practice: PhotoVoice is ideal for use within mental health nursing as it coincides with the recovery principle of promoting collaborative partnership between service users, family members and clinicians. Mental health nurses work directly with service users and family members throughout their recovery journey. The PhotoVoice methodology is coherent with the recovery principles of empowerment, collaboration and prioritizing the lived experiences of the individual. As such, this methodology has the potential to enhance greatly what mental health nurses can know and understand about the lived experiences of service users and family members. In turn, engaging with the PhotoVoice methodology can provide a platform from which further collaborative engagement between service users, family members and clinicians can take place.